Viability of Street Vending Business-A case study on twin cities of Hyderabad - Indira, Dr. D.; Kiran, D.Ravi; Satyavani, Dr.B.; Raju, Dr.S.V.S.S. Srinivasa; G.Vandana (The journal of contemporary issues in business and government, 2021)
Street Vending has been the bread winning profession for the urban poor which has existed since time immemorial all around the world and has also contributed significantly to economies. There have been number of studies describing the profile, problems and socio- economic conditions faced by street vendors, this study looks at the street vendor as a businessman and assesses the viability of the trade. It is an exploratory and analytical study wherein data has been collected from primary and secondary sources. Purposive sampling was used as the number of units in the population are infinite and a sample size of 800 was chosen. The study found that street vending is a profitable business as majority of the respondents were able to meet their monthly expenditure, buy durable goods and some of them were able to buy fixed property like house and land. Hence Street Vending is an important profession to be examined carefully by policy makers.